Is generalized trust related to mistrust of university health care centre? - Harris Shah Abd. Hamid; Azlin Hj Alwi; Wan Fatin Munira Wan Mustapha (Penerbit Universiti Kebangsaan Malaysia, 2018)
Personal characteristics like gender has been shown to be related to people’s attitude towards medical treatment. A negative attitude towards health care provider can be expressed as mistrust. This paper examines the relationship between personal characteristics (generalized trust, sex including whether the person had obtained treatment at a health care centre) and mistrust to a university health care centre. Survey respondents are 420 university students with age ranging from 18 to 29 (M=21.6, SD=1.26). Both types of trusts were similar between the sexes and between students who had and had not visited the health care centre. The finding reveals that generalized trust is not related to mistrust towards healthcare provider. Further studies are needed to establish the extent to which a domain-specific mis-trust has marginal benefits over a generalized trust